Community Empowerment in Environmental Management Through the Opetapika Program - Siti Jamilah; Nur Indah Tri Yanuar Puspita; Muhammad Ilham Mauludi; Infik Ivadatun Qomariyah; Reza Hilmy Luayyin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The issue of pollution along the Paser River, caused by the community’s habit of indiscriminately disposing of waste, prompted KKN students to design the Operasi Taman Pinggir Kali (OPETAPIKA) program as a community-based empowerment initiative. This study aims to analyze the effectiveness of Opetapika by employing the Participatory Action Research (PAR) method, which actively involves the community in every stage of the program. The findings reveal that Opetapika successfully transformed the riverbanks once filled with waste into a simple, clean, and green riverside park, while simultaneously fostering community participation, a sense of ownership, and collective responsibility for environmental sustainability. Despite challenges in maintaining consistent participation, the direct involvement of residents and students proved effective in encouraging behavioral change. Thus, Opetapika can be concluded as a sustainable environmental empowerment model with strong potential for replication in other regions facing similar challenges.